Traffic Volume Patterns in Urban Areas (Case Study: Sungguminasa City Border Road - Takalar Regency Border Road Km 0-3.41) - Gusty, Sri; Chaerul, Muh.; Puspitarini, Made Dianing (ASTONJADRO, 2024)
Pallangga District is the district with the second largest population in Gowa Regency, with a population of 133,027 people or 16.84 percent of the total population in Gowa Regency (Gowa Regency Central Statistics Agency, 2023). The rapid development of housing and commerce has made Pallangga District the most populous area apart from the district capital, namely Sungguminasa. This has also led to changes in land use and an increase in traffic volume, causing congestion. The development of housing and commerce has generated travel generation and attraction around the Sungguminasa City Border Road - Takalar Regency Border Road, but this has not been followed by an increase in transportation facilities and infrastructure, especially road capacity. This shows that land use planning and transportation planning have a relationship that mutually influences each other. This research aims to determine the traffic volume on Jalan Batas Kota Sungguminasa-Batas Kota Takalar Km 0-3.41. The research method used is quantitative analysis by conducting traffic volume surveys and using the 2023 Indonesian Road Capacity Guidelines (PKJI, 2023) as a reference. The results of the research show that road capacity and traffic volume influence the occurrence of traffic jams on the Sungguminasa City-Batas City Border Road, Takalar Regency.